ANALISIS BIBLIOMETRIK TREN DAN KEBAHARUAN STUDI PERMEABILITAS DENGAN CHEMINFORMATICS BERBASIS DATAWARRIOR - Matthew Valentino, Tambunan; Putri, Mulan Gevika Amara; Damayanti, Ni Ketut Anggun; Sianturi, Tiarma Kristiana (Acta Pharmaceutica Indonesia, 2025)
Cheminformatics is a discipline that employs computational methods on chemical data and has emerged as a cutting-edge approach in pharmaceutical sciences. DataWarrior, an open-source software that integrates big data, offers a variety of features to support cheminformatics studies. This study aims to examine permeability research using DataWarrior-based cheminformatics and evaluate the potential for research innovation, particularly within the field of pharmacy. A bibliometric analysis using the Dimensions, Biblioshiny, and ResearchRabbit databases reveals that publications on permeability studies employing DataWarrior have increased, although the number of citations has declined due to a lack of novelty in the topics. Moreover, the limited use of the keyword "cheminformatics" in permeability studies indicates that the connection between these two fields needs to be strengthened. The integration of pharmacokinetic and physicochemical data via DataWarrior enables the development of more reliable methods by enhancing the prediction of compound similarity through its built-in descriptors, thereby supporting the practicality of molecular permeability and pharmacokinetic studies for new compounds. On the other hand, this research potential for Indonesia to increase its contributions to publications and citations in this field.